Cost Efficiency for Load Devices Based on IOT - Seema,; Rajkumar, (International Journal of Computer Sciences and Engineering, 2019)
Internet of Things or IoT is an interconnected network of physical devices connected to each other through the internet. The ‘things’ here refer to the physical object in the network that has its own unique IP address and has the ability to send and receive data over the network. It is a growing topic of interest these and will deeply affect our daily life. This thesis work aims to apply the IoT paradigm for controlling and monitoring of a smart lighting application. The implementation aims to reduce the energy consumption in addition to, achieve adaptability of the lights according to the surrounding environment. The implementation uses Service Oriented Architecture (SOA) to allow heterogeneity and interoperability between components.